Interferensi Bahasa Indonesia dalam Penguasaan Bahasa Arab: Studi Kasus Santri Ma’had Lughah Cileunyi, Kabupaten Bandung / Interference of Indonesian Language in Arabic Language Mastery: A Case Study of Students of Ma'had Lughah Cileunyi, Bandung Regency - Wildan Rinanda Komara; Syifa Fata Auliya Gunawan; Silvia Tsamratul Fu'adah; Zulli Umri Siregar (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study analyzes Indonesian language interference in Arabic acquisition among students at Ma’had Lughah and identifies its causes and solutions. The interference includes errors in phonology, morphology, and syntax, mainly due to geographical background, limited Arabic interaction, dominance of Indonesian structures, and lack of self-directed learning. Using a descriptive qualitative approach with observation, interviews, and text analysis, the study involved 23 students from various regions, including Jabodetabek, Bandung Raya, and outside Java. Seventy-two errors were found in reading texts, such as letter substitutions, omissions, and incorrect harakat pronunciations. Common mistakes include pronouncing ‘ain as hamzah and qaf as kaf. The main cause of interference is the dominance of Indonesian as the everyday language and medium of instruction, influencing Arabic patterns. Proposed solutions include regional-based phonology training, more daily Arabic interaction, additional tajwid classes, and enhancing self-directed learning using digital media. The study provides insights and suggests strategies to improve Arabic proficiency.المستخلص: تهدف هذه الدراسة إلى تحليل تدخل اللغة الإندونيسية في اكتساب اللغة العربية بين الطلاب في معهد اللغة وتحديد الأسباب والحلول. تتضمن التدخلات الأخطاء في الصوتيات والصرف والنحو، ويرجع ذلك أساسًا إلى الخلفية الجغرافية، وقلة التفاعل بالعربية، وهيمنة بنية اللغة الإندونيسية، ونقص التعلم الذاتي. استخدمت الدراسة منهجًا وصفيًا نوعيًا مع الملاحظة، والمقابلات، وتحليل النصوص، وشارك فيها 23 طالبًا من مناطق متنوعة مثل جابوديتابيك، بانجونغ رايا، وخارج جزيرة جاوة. تم تحديد 72 خطأ في قراءة النصوص، مثل استبدال الحروف، وحذف الحروف، والأخطاء في نطق الحركات. تشمل الأخطاء الشائعة نطق عين بهمزات ونطق قاف بـ كاف. السبب الرئيسي للتدخل هو سيطرة اللغة الإندونيسية كلغة يومية ووسيلة تعليمية، مما يؤثر على استخدام اللغة العربية. تشمل الحلول المقترحة تدريبًا صوتيًا بناءً على الخلفية الإقليمية، وزيادة التفاعل اليومي بالعربية، ودروسًا إضافية في التجويد، وتعزيز التعلم الذاتي باستخدام الوسائط الرقمية.